Tamoxifen for treatment of abnormal uterine bleeding in etonorgstrel implant users: a randomized clinical trial - Fetih, Ahmed N.; Abbas, Ahmed M.; Kamel, Fatma A.; El Nashar, Ihab H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The current study aims to compare the use of tamoxifen and oral contraceptive pills in women using implanon and complain with irregular uterine bleeding. Methods: Women attended family planning clinic using implanon presented by bleeding were invited to participate in the study. They were randomized into two groups: Group A: 100 women received Tamoxifen 10 mg twice daily for 10 days taken at the onset of an episode of bleeding or spotting episode. Group B: 100 women received Combined oral contraceptive pills (microcept) once daily for 21 days take at the onset of an episode of bleeding or spotting episode. Results: No difference regarding the baseline criteria of both groups. No difference between both groups regarding the duration of irregular bleeding in the implanon users (p=0.090). Additionally, the number of bleeding days and spotting in the last month was similar in both groups (p=0.554). The percentage of women who stopped bleeding during the period of treatment is 84% in the tamoxifen group and 92% in the COCs group, but the COCs needs longer treatment time, where the mean of days required to stop bleeding is 5.03±1.8 days in the tamoxifen group and 6.5±2.5 in the COCs group. Headache and nausea were the most prominent adverse effects found in the COCs group (p=0.000). Conclusions: Oral administration of tamoxifen 10 mg twice daily for 10 days is effective on stopping bleeding attacks in implanon users.